(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
Even though conceptually close, it is a fact that the world of publishers and the world of scholars are still very different. They pursue different purposes: while publishers’ goal is trade, scholars’ aim is to provide correct texts. Readers, instead, have gradually become less demanding, because they got used to low quality books. Texts are a common good, a cultural and social instrument of growth: it is necessary to spread this idea to the new generations.